1996
DOI: 10.1080/00343409612331349728
|View full text |Cite
|
Sign up to set email alerts
|

Labour Regulation and Enterprise Strategies in the South African Clothing Industry

Abstract: ALTMAN M. (1996) Labour regulation and enterprise strategies in the South African clothing industry, Reg. Studies 30, 387-399. This paper explores the impact of regional differences in labour regulation on the accumulation strategies of firms in the South African clothing industry. A strong positive relationship was found between dominant accumulation strategies and forms of local regulation. In the context of a footloose industry, South African clothing firms should have been able to make use of differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Moreover, new technologies, such as computer aided design, mechanized laying-up or cutting, facilitates the adoption of unit production systems, which greatly enhance efficiency. Altman's (1996) research disclosed important spatial variations across South Africa in the extent to which such changes were occurring in factory production. Overall, it was found that clothing firms based in the Johannesburg or Durban metropolitan areas "were very slow to implement process innovations or skills development" programmes (Altman, 1996, p. 393).…”
Section: The National Context: Restructuring the S 0 Uth African CL 0mentioning
confidence: 98%
See 4 more Smart Citations
“…Moreover, new technologies, such as computer aided design, mechanized laying-up or cutting, facilitates the adoption of unit production systems, which greatly enhance efficiency. Altman's (1996) research disclosed important spatial variations across South Africa in the extent to which such changes were occurring in factory production. Overall, it was found that clothing firms based in the Johannesburg or Durban metropolitan areas "were very slow to implement process innovations or skills development" programmes (Altman, 1996, p. 393).…”
Section: The National Context: Restructuring the S 0 Uth African CL 0mentioning
confidence: 98%
“…Like much of South African industry, the manufacture of garments is oriented towards the domestic market which "appears to operate as a buyer-driven commodity chain" with major clothing retailers assuming a critical role (McCormick, 1999c, p. 15). At the heart of the weakness of the South African clothing industry is the question of low productivity (Altman, 1994(Altman, , 1996. It is argued by Altman (1994, p. i) that the industry competitiveness of the clothing sector is depressed by what is termed "a highly traditional outlook on productivity improvement".…”
Section: The National Context: Restructuring the S 0 Uth African CL 0mentioning
confidence: 98%
See 3 more Smart Citations